Bacterial Diversity in Buffalo Meat and Bowel from Traditional Market and the Sensitivity of Some Bacteria to Irradiation and Antibiotics - H. Harsojo; S.Y. Sari (Atom Indonesia, 2015)
The population of buffaloes in Indonesia was 1.37 million in 2012, representing an increase of 5.5 % over its population the previous year. Buffaloes have been in Indonesia for such a long time, they have become a part of the lives of the majority of the Indonesian society. Research has been conducted to know the bacteria diversity in domestic buffalo meat and bowels from traditional markets in Pandeglang, Banten, in order to ascertain their safety based on their initial contamination and also to study the sensitivity of several of the bacteria to irradiation and antibiotics. The total bacterial was assessed by total plate count method as index of quality. The buffalo meat and bowel samples were taken from livers, intestines, lymph, lungs and tripe. Results showed that the contaminating bacteria were aerobic bacteria, coliform bacteria including Escherichia coli (E. coli), and Staphylococcus spp. in buffalo meat and bowel. The numbers of aerobic bacteria were in the 1.7×105- 2.3×106 CFU/g range, while the total coliform bacteria were in the 2.0×103- 6.8×104 CFU/g range. The total number of E. coli was in the 2.0×103- 6.0×104 CFU/g range, and Staphylococcus spp. was in the 2.0×104- 2.7×105 CFU/g range. No Salmonella was detected in any of the samples observed. The total coliform bacteria, E. coli, and Staphylococcus spp. in all buffalo meat and bowel samples exceeded the maximum numbers of microbes permitted by the Indonesian National Standard (SNI). The maximum of total coliform, E. coli, and Staphylococcus spp. permitted by SNI are 1.0×102, 1.0×10 and 1.0×102 CFU/g, respectively. The D10 values of S. aureus were in the 0.13 - 0.23 kGy range, while for E. coli they were in the 0.07 - 0.13 kGy range. The isolate of S. aureus from the lungs was the most resistant to cefoxitin, tetracycline, and amoxicillin antibiotics. The isolate of E. coli from buffalo bowels were almost sensitive to cefoxitin, tetracycline, and amoxicillin antibiotics.  Received: 4 October 2014; Revised: 24 April 2015; Accepted: 11 May 2015